2020
DOI: 10.1021/acs.inorgchem.0c00664
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Site-Selective Doping in SrSnO3:Eu Oxides and Its Impact on the Crystal and Electronic Structures Using Synchrotron Radiation and DFT Simulations

Abstract: The impact of Eu3+ doping at the Sr2+ and Sn4+ sites in SrSnO3 on its structural and electronic properties was studied and correlated with the photocatalytic efficiency. The compounds were synthesized using a modified Pechini method. Refinement of the synchrotron X-ray diffraction (S-XRD) data showed that the samples had an orthorhombic Pbnm symmetry. The incorporation of Eu into the lattice led to increased short- and long-range disorder, inducing additional distortion in the SnO6. XANES measurements revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 73 publications
(136 reference statements)
0
26
0
Order By: Relevance
“…Subsequently, with the use of a Shimadzu UV-1800 spectrophotometer, it was possible to analyze the resulting solution based on UV-Vis absorption spectroscopy over a wavelength scan ranging from 240 to 800 nm. As a result, the ultimate concentration of the solution could be derived through observing the largest absorption band of phenol at 271 nm following Equation (7), proposed by Rahman et al [33] and Chantelle et al [34]:…”
Section: Photocatalytic and Absorption Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, with the use of a Shimadzu UV-1800 spectrophotometer, it was possible to analyze the resulting solution based on UV-Vis absorption spectroscopy over a wavelength scan ranging from 240 to 800 nm. As a result, the ultimate concentration of the solution could be derived through observing the largest absorption band of phenol at 271 nm following Equation (7), proposed by Rahman et al [33] and Chantelle et al [34]:…”
Section: Photocatalytic and Absorption Experimentsmentioning
confidence: 99%
“…The Zn, and O are 4.67%, 9.24%, 61.22%, and 24.87%, respectively. The a peaks in the EDS indicates the CdO/ZnO/Yb2O3 NSs product is exclu Cd, Yb, Zn, and O [34].…”
Section: Analysis Of Morphology and Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A and B site cations in the perovskite lattice give a broader scope to tailor the structure and properties of photocatalyst, however, the conventional "trial and error" approach reduces the efficiency of developing novel materials. The theoretical calculation based on density functional theory (DFT) provides relevant insights into theoretical electronic band structures to uncover the structure-property relationship, which can be used to predict the photocatalytic performance and lays a good foundation for the rational development of effective new perovskite oxide photocatalyst [311][312][313] .…”
Section: Theoretical Calculation Of Perovskite Oxide Photocatalystmentioning
confidence: 99%
“…The presence of oxygen vacancies also improves the migration of photogenerated electrons and holes to the surface and their rapid transfer to the catalytic sites [61]. Recently, our research group [63] showed that Eu doping into SrSnO3 lattice increased short-and long-range order, induced a distortion in the SnO6 and created Eu midgap states. All these factors apparently favored charge separation and improved the photocatalytic activity.…”
Section: Figurementioning
confidence: 99%